LANGUAGE ATTITUDE OF THE ENGLISH DEPARTMENT STUDENTS TOWARD ENGLISH - Marlina Muhammad Tangke (Teaching English as a Foreign Language Overseas Journal, 2022)
The objective of this research was to determine the language attitudes of the English Department students towards English. The research method applied in this research is quantitative method. The subjects of this research were students of the English Department at UKI Toraja from the 2017, 2018 and 2019 academic years. Data collection was carried out through distributing questionnaires consisting of 12 statements. Furthermore, the data obtained were analyzed using a Likert scale calculation used to measure these aspects which consisted of 5 (five) scales. The results of this research found that there were two main categories of students’ language attitudes, namely positive and negative attitudes. Respondents consisted of 25 students in the 2017, 2018 and 2019 academic years who filled out a statement questionnaire. Most of the students strongly agree and agree or have a positive attitude towards English. They know the importance of English in this global era, are proud to learn English, and love to use English. Therefore this study suggests, to do more research and studies on the language attitudes of English Department students towards English.